Cultural Riddles and Performance in Modern African Societies - Akporherhe Friday; Udi Peter Oghenerioborue (Randwick International of Social Science Journal, 2023)
Several forms of performance arts are underutilized for in the past few decades and the Urhobo riddles are not left out. This paper therefore examines various methods of preservation and transfer of riddles in traditional society. This study adopted the survey-descriptive approach as the data and information were collected from natural environment and analysed. It is underpinned by Sigmund Freud’s psychoanalytic theory that focuses on the unconscious mind of people as the storehouse of latent materials which can be activated and brought to the conscious awareness. The information were collected with sound recordings which were afterward deciphered and deciphered from the Urhobo dialect into the English adaptation. In-depth interviews were also conducted to obtained first-hand information from respondents. The respondents were purposively selected and interviewed. The data collected in the field were qualitatively analyzed using descriptive and analytical methods. Findings reveal that riddles perform utilitarian functions like entertainment, education, knowledge transfer, coping and distractive strategies and so on. These linguistic resources should be preserved and documented due to their cultural values. Though there are problems hindering the growth of the riddles in contemporary societies, orators have devised the use of popular music as new way of preservation and transferring of oral traditions like the riddles from going into extinction.